Embodiment of Environmental Motifs in Enriching Contemporary Fine Artwork (Al-Farooq Journal of Sciences, 2026)
This research examines the embodiment of environmental motifs in enriching contemporary fine artwork, based on the significant transformations that contemporary art has witnessed in relation to environment, material, place, and aesthetic awareness. In contemporary artistic practice, the environment is no longer treated merely as an external subject to be represented or imitated; rather, it has become a visual, material, and symbolic source that contributes directly to the structure of the artwork itself. This includes natural elements, environmental materials, recycled waste, and symbols associated with place, identity, and ecological awareness. The research problem lies in the fact that many artistic approaches have dealt with the environment as a visual background or representational theme, while there remains a need for an analytical reading that explains how environmental motifs become active formative elements that enrich contemporary artwork in terms of composition, texture, meaning, expression, and environmental consciousness. The research aims to define environmental motifs, identify their role in enriching aesthetic and visual values, and analyze their relationship with environmental art, contemporary art, and sustainability. The study adopts the descriptive analytical method by reviewing relevant literature and analyzing selected artistic tendencies that rely on environmental motifs and materials. The research concludes that environmental motifs represent an important visual and aesthetic approach for expanding artistic experimentation, deepening the artist’s relationship with place, nature, and identity, and promoting environmental awareness. They also transform artwork into a contemporary visual discourse that combines beauty with responsibility.
Keywords: Environmental motifs, fine artwork, contemporary art, environmental art, environmental materials, visual formation, aesthetic sustainability